"Navigating through" : a grounded theory of the development of ethical practice in undergraduate nurses : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Nursing - Vallance, Esther (Massey University, 2003)
This thesis presents an exploration of the perspectives of nine newly graduated registered nurses on their undergraduate ethics education in preparation for practice as registered nurses. Data gathered from interviews, document audit and a literature review structure this research. Grounded theory methodology was utilised to analyse the comprehensive data gathered during the research process and resulted in a theoretical description and explanation of the process of learning ethics and ethical practice during three years of undergraduate nursing education. Nursing practice has an ethical component that is, on a daily basis, significant and challenging. To this end, one of the key tasks of undergraduate nursing education is to adequately prepare its 'neophytes' for the ethical demands of practice. To date, very few studies have investigated the ethics preparation for student nurses, particularly in New Zealand. This study aims to partially redress this lack by offering insights into undergraduate ethical learning. The findings of this study revealed that participants learned ethics and ethical practice through faculty education, role modelling nurses in practice, journaling and reflection tutorials, and experimentally. It was also found that participants held 'ethical ideals' that reflected the patient-focused professional ethical values developed during their nursing education. These 'ethical ideals' were held as a standard and a guide to practising ethically. Participants' ethical perspectives widened as they began to 'test their ideals' in the 'real world' of nursing practice and perceive contextual obstacles that confronted them. Thus, it was found that the 'ideal' was problematic to enact in the 'real' world of nursing practice. Hence, 'navigating through' emerged as the core process that was adopted by participants as they endeavoured to preserve their 'ethical ideals', negotiate contextual obstacles and successfully reach graduation This meant that they endured a measure of 'powerlessness' to impact ethically upon the contexts that they found themselves in. It is envisaged that the findings from this project may inform undergraduate nursing education as to how to better prepare its neophytes for the ethical demands of practice.
Keywords: Nursing ethics; Nursing